Local SAR, global SAR, and power‐constrained large‐flip‐angle pulses with optimal control and virtual observation points. Issue 1 (30th December 2015) - Vinding, Mads S.; Guérin, Bastien; Vosegaard, Thomas; Nielsen, Niels Chr.
Abstract : Purpose: To present a constrained optimal‐control (OC) framework for designing large‐flip‐angle parallel‐transmit (pTx) pulses satisfying hardware peak‐power as well as regulatory local and global specific‐absorption‐rate (SAR) limits. The application is 2D and 3D spatial‐selective 90° and 180° pulses. Theory and Methods: The OC gradient‐ascent‐pulse‐engineering method with exact gradients and the limited‐memory Broyden‐Fletcher‐Goldfarb‐Shanno method is proposed. Local SAR is constrained by the virtual‐observation‐points method. Two numerical models facilitated the optimizations, a torso at 3 T and a head at 7 T, both in eight‐channel pTx coils and acceleration‐factors up to 4. Results: The proposed approach yielded excellent flip‐angle distributions. Enforcing the local‐SAR constraint, as opposed to peak power alone, reduced the local SAR 7 and 5‐fold with the 2D torso excitation and inversion pulse, respectively. The root‐mean‐square errors of the magnetization profiles increased less than 5% with the acceleration factor of 4. Conclusion: A local and global SAR, and peak‐power constrained OC large‐flip‐angle pTx pulse design was presented, and numerically validated for 2D and 3D spatial‐selective 90° and 180° pulses at 3 T and 7 T. Magn Reson Med 77:374–384, 2017. © 2015 Wiley Periodicals, Inc.